2022
DOI: 10.1186/s13089-021-00256-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of point-of-care ultrasonography (POCUS) in the diagnosing of acute medial meniscus injury of knee joint

Abstract: Background In recent years, musculoskeletal ultrasound has increasingly become the common method for diagnosis for many medical specialties. Therefore, the present study was performed to evaluate the diagnostic value of point-of-care ultrasonography (POCUS) as a primary triage tool in the diagnosis of the acute medial meniscus injury of the knee. Materials and methods The present cross-sectional study was performed on patients with a suspected medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…First, the US resolution has improved in recent years. Second, the linear array probe resolution used in recent years is higher than the convex array probe resolution [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the US resolution has improved in recent years. Second, the linear array probe resolution used in recent years is higher than the convex array probe resolution [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, a wide range of sensitivity and specificity of US for the diagnosis of meniscal injuries has been reported [1,[15][16][17]. In addition, several studies have demonstrated the diagnostic accuracy of US to be poor and inappropriate compared to MRI for diagnosing meniscal tears [2,18,19], while some have shown them to be very useful and suitable [8,12,20]. This study was conducted in the ED, and POCUS was performed by the attending emergency medicine doctor.…”
Section: What Is New In the Current Studymentioning
confidence: 99%
“…Reports such as these support that USI is a valuable point-of-care imaging modality tool to extend the physical examination in the physical therapy clinic. [61][62][63] There were several case reports where the resulting diagnosis was vascular pathology. 22,25,36,45 These vascular-related case reports suggest that PTs should maintain a high degree of suspicion for these differentials, and Doppler might be an appropriate imaging modality for some physical therapy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent reports have investigated the joint synovial cavity in knees with hydrarthrosis and/or knee pain using non‐contrast‐enhanced MRI (De Kaneko et al, 1993; Wang et al, 2016). Among these examinations, ultrasonography is noninvasive, simple, and allows dynamic evaluation (Ahmadi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%